Helena Antipoff, as Sociedades Pestalozzi e a educação especial no Brasil - Rafante, Heulalia Charalo (2011)
In this study we analyze Helena Antipoff s trajectory in order to understand her participation, as well as that of institutions created by her, in the construction of Special Education in Brazil. We investigate everything from the first specialized educational establishments to the creation of the National Center for Special Education (CENESP) in 1973, and present the context in which Antipoff s ideas and practices were introduced in the national scenario, as well as the conditions that led to their continuation. This is a research based on documentary sources where we deal with Special Education, taking as reference both education in general and the different historical contexts in Brazil, with their social, political and economic particularities. To start with, we present the trajectory of the Russian psychologist and educator Helena Antipoff, highlighting the theoretical and methodological principles of her education and what brought her to Brazil in 1929. In the second chapter, we deal with the history of Brazilian Special Education, where we present the first institutions created; the influence of the movements of the New School and Mental Hygiene in the configuration of demands for special education; and also, the main actions directed to "exceptional" children in the first four decades of the twentieth century. In the third chapter, we relate Antipoff s actions in Minas Gerais with the Brazilian historical context in the 1930s and 1940s and assess the motivations that led the educator to create institutions that met the needs of "exceptional" children. In the fourth chapter, we investigate the factors that led Helena Antipoff to go to the National Child Department in the Federal District in 1945; her performance in that department; and the creation of the Pestalozzi Societies of Brazil (1945) and of the State of Rio de Janeiro (1948). In Chapter V, we analyze the issues of the proceedings Seminars on Exceptional Children, coordinated by the Pestalozzi Societies (1951, 1952, 1953, 1955), in order to understand the spread of the educator s ideas throughout the country. In the last chapter, we focus on the initiatives by the federal government in the 1960s and early 1970s related to Special Education in order to identify the impact of Helena Antipoff s propositions in that respect. We conclude that the actions taken by her in Brazil with the creation of the Pestalozzi Societies in the several States (1932 - MG, 1945 - DF, 1948 - RJ; 1952 - SP 1954 - BA, 1955 - GO), were crucial in bringing about the problematics of education of "exceptional" children. These institutions acted by informing the public about the types of "abnormalities" and their possible care, by training specialists in the field, and also by claiming public funds to finance programs pertaining to the area. This process culminated in the four proceedings Seminars on Exceptional Childhood, whose developments influenced the federal government to establish: (a) The National Campaigns of Education, introducing the theme of education of "exceptional" children; (b) the inclusion of Special Education in the Guidelines and Bases of National Education Law (no. 4024/61); and (c) the institutionalization of the National Week of Exceptional People (1964). This scenario depicts a concrete demand for the institutionalization of Special Education at the national level, which was not materialized in an autonomous way for Education in Brazil until the early 1970s. It was only in the wake of the implementation of Law number 5692/71, whose goal was the universalization of education, in general, from 7 to 14 years of age, that Special Education was included in the Sectorial Plan of Education (1972-1974), through Priority Project number 35. This project was developed under the influence of what was being done in the field of Special Education in Brazil, mainly by the Pestalozzi Societies, but also received significant influence from the MEC-USAID agreements and determinations by the UN for this sector. It was in order to run this project that CENESP was created.